BEE FLORAL CALENDAR OF CULTIVATED AND WILD PLANTS AVAILABLE IN DIFFERENT AGROECOSYTEMS OF CHITWAN, NEPAL - Rijal, Shiva P.; Thapa, Resam B.; Sharma, Moha D.; Sah, Shrawan K.; GC, Yubak Dhoj (International Journal of Research -GRANTHAALAYAH, 2018)
Beekeeping is one of the promising enterprises for economically poor farmers in Nepal but beekeeping farmers lack flora calendar for pollination, bee foraging, and honey production. Therefore, a study was conducted visiting farmers’ fields every 15-20 days during 2012-2013 to monitor the common plant species visited by bees, which were considered as bee forage plants categorized as major, and minor sources of pollen and/or nectar. Relevant information was also gathered through key informant interviews and group discussions. During the study period a total of 252 plant species were recorded and their floral calendar prepared. In the study area. The main species identified were: rice, Oryza sativa L.; maize, Zea mays L.; buckwheat, Fagopyrum esculentum Moench.; rapeseed, Brassica campestris L.; sesame, Sesamum orientale L.; litchi, Litchi chinensis Sonner; and cucurbits (bottle gourd, Lagenaria siceraria (Molina) Standl; sponge gourd, Luffa cylindrica (L.) Roem.; bitter gourd, Momordica charantia L.), Leucas (gumpate), Leucas lanata Benth.; Butternut (chiuri), Bassia butyracea Roxb.; Pogostemon (rudilo), Pogostemon glaber Benth.; guava, Pisum sativum L; Sisoo, Dalbergia sissoo Roxb.; Throughwort (Banmara), Eupatorium sp.; silk tree (Padke), Albizia julibrissin Durazz ; Terminalia (Saj) Terminalia bellirica (Geartn.) Roxb. and Murraya (kadipatta) Murraya koenigii (L.) Spreng. Species of Brassica, Pogestemon, Bassia, Citrus, and Artemisia, Pisum, Ipomoea and Eupatorium species were some of the important plants which bloomed during winter. And, Lagerstroemia sp., Impatiens sp, Sesamum indicum L., Zea mays L., Albizia sp. and many cucurbits bloomed during rainy season. Fagopyrum esculentum Moench, Brassica campestral L, Lagerstroemia indica L, Bombax ceiba L, Albizia julibrissin Durazz., Eugenia formosa Wall., Shorea robusta, Guartn. Upatorium grandulosum, Pogostemon glaber Benth. Terminalia alata Heyne ex.Roth, Murraya koenigii (L.) Spreng Sesamum orientale L. Dalbergia sissoo Roxb. were the major bee flora both rich in nectar and pollen.